Knowledge about NCD in medical students and screening for their nutritional status - Bhave, Swati Y.; Adsul, Srushti S.; Bhawalkar, Jitendra S.; Mane, Shailaja V.; Landge, Jyoti (International Journal Of Community Medicine And Public Health, 2023)
Background: Creating awareness about NCD prevention and screening medical students’ nutritional status will help them to follow a healthy lifestyle. Thus, ensuring that as future doctors, they will be effective in community education of NCD prevention through their own health. Methods: A two-hour awareness session was taken for 150 medical students to explain importance of assessing their risk factors for NCD. The age range was 18-21 years. They were offered a free health check-up and 89.33% (136) signed up. For screening of obesity - anthropometric measurements were taken 1) weight by electronic weighing scale 2) height- using analog measuring tape 3) waist hip measurement 4) body fat composition measured by Omron (Karada scan- body composition monitor HBF-375). BMI was calculated using both WHO and Asian cut-offs and waist circumference using WHO and ICMR cut-offs. Results: In 132 (M=55, F=79) participants, significant incidence was seen of overweight (21.21%), obesity (43.18%) by Asia Pacific BMI standards and 36.36% overweight, 36.36% obesity by total body fat measurement. Abdominal obesity measured by waist circumference was seen in 3.22% of males and 21.52% of females by WHO; 15.09% of males and 41.77% of females by ICMR standards. Females showed a higher incidence of obesity and overweight than males according to Asia Pacific BMI, total fat percent and ICMR waist circumference. Conclusions: These students will benefit from interventions to inculcate a healthy lifestyle and maintain a healthy weight. Healthy medical students tracking into healthy doctors will act as ambassadors for NCD prevention.